Effects of the Biopesticide Spinosad on Eristalis tenax Brain and Motor skills - Jansson,Edit (2025)
The extensive use of pesticides within the agricultural landscape is essential for maintaining sufficient yields and sustaining our growing population, however, their widespread use is not without costs. Increasing evidence shows that pesticides harm many non-target organisms, including those providing vital ecosystem services. Pollinators, for instance, are critical for the fruiting of nearly 75% of major food crops globally, yet worryingly their populations are declining, with pesticide use identified as a key driver. It has been suggested that pesticides derived from natural origins, biopesticides, are less harmful than synthetic alternatives and therefore offer a promising way to minimize this negative effect. In this study, I investigated the effects of chronic exposure to field realistic doses of a biopesticide, spinosad, on hoverfly and common pollinator Eristalis tenax. Flies were exposed for 20 days to either a control treatment or a spinosad treatment (0.2 ppm), both provided ad libitum. On days 2, 9, and 20, randomly selected individuals from both treatments were subjected to behavioral assays and brain imaging, to link potential neuroanatomical changes with any behavioral impairments. Results revealed that chronic exposure to 0.2 ppm spinosad significantly increased mortality, in E. tenax. Furthermore, for the surviving individuals, spinosad treated flies had significantly higher occurrence of brain vacuolation at day 9 and 20, than in control flies. Moreover, spinosad caused a decreased visually guided turning response in E. tenax already at day 2, along with a progressive decline in overall activity. These results indicate that field-realistic concentrations of spinosad, legal for use in organic farming, impair brain physiology, sensory processing, and locomotor activity in an important non-target pollinator.